2011
DOI: 10.1093/infdis/jiq054
|View full text |Cite
|
Sign up to set email alerts
|

Functional Quorum Sensing Systems are Maintained during Chronic Burkholderia cepacia Complex Infections in Patients with Cystic Fibrosis

Abstract: Quorum sensing (QS) contributes to the virulence of Pseudomonas aeruginosa and Burkholderia cepacia complex lung infections. P. aeruginosa QS mutants are frequently isolated from patients with cystic fibrosis. The objective of this study was to determine whether similar adaptations occur over time in B. cepacia complex isolates. Forty-five Burkholderia multivorans and Burkholderia cenocepacia sequential isolates from patients with cystic fibrosis were analyzed for N-acyl-homoserine lactone activity. All but on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 44 publications
1
15
0
Order By: Relevance
“…In contrast to P. aeruginosa , McKeon et al showed that B. cenocepacia QS mutants were far less frequent during chronic infection. Only 1 in 22 patients harboured mutations in both QS Bcc systems, cepR and cciR, which would have an effect on function, the loss in QS function did not appear to confer a competitive advantage for B. cenocepacia in vivo [ 106 ]. Recent data showed that a triple knock-out mutant in J2315 of cepl, cciR and Burkholderia diffusible signal factor, had reduced biofilm forming capacities, was more susceptible to antibiotics, and was less virulent in C. elegans than the wild type strain [ 107 ], which may explain the lack of QS mutants in chronically colonised CF patients.…”
Section: Quorum Sensingmentioning
confidence: 99%
“…In contrast to P. aeruginosa , McKeon et al showed that B. cenocepacia QS mutants were far less frequent during chronic infection. Only 1 in 22 patients harboured mutations in both QS Bcc systems, cepR and cciR, which would have an effect on function, the loss in QS function did not appear to confer a competitive advantage for B. cenocepacia in vivo [ 106 ]. Recent data showed that a triple knock-out mutant in J2315 of cepl, cciR and Burkholderia diffusible signal factor, had reduced biofilm forming capacities, was more susceptible to antibiotics, and was less virulent in C. elegans than the wild type strain [ 107 ], which may explain the lack of QS mutants in chronically colonised CF patients.…”
Section: Quorum Sensingmentioning
confidence: 99%
“…Interestingly, all but one isolate produced AHLs. Further analyses revealed that there is a selective advantage for strains with a functional CepIR system and that mutations in these genes are therefore very rare 75 . Additional evidence for an important role of AHL-mediated QS was obtained by analyzing the transcriptome of two clonal variants of B. cenocepacia isolated during long-term colonization of a CF patient 76 .…”
Section: The Role Of Qs In Pathogenicity Of Members Of the Bccmentioning
confidence: 99%
“…in ET12 strains) [5], [7]–[10]. Both systems appear to be maintained during chronic infections in CF patients [11]. CepI primarily synthetizes oxanoyl-homoserine lactone (C8-HSL) and minor amounts of hexanoyl-HSL (C6-HSL), whereas CciI is primarily responsible for the synthesis of C6-HSL with lesser amounts of C8-HSL [8].…”
Section: Introductionmentioning
confidence: 99%